Anopheles gambiae complex: Molecular forms and occurrence of the KDR gene in rural Southwestern Nigeria (2011)
An investigation focusing on the molecular forms of Anopheles gambiae complex and occurrence of the knockdown resistance (kdr gene) was carried out from June to July 2001 and August to September 2002 at Igbo-Ora, Nigeria usirig aspirator and DNA analyses. Of the 127 An. gambiae s. l. analysed, there were 66 (51:9%)M and 61 (48.03%) S forms, both recorded in An. gambiae s.s. and Anopheles arabiensis. The forms were virtually sympatric throughout the study. Two of the An. gambiae s.s. examined harboured the kdr gene (RR, RS). The occurrence of the kdr gene at Igbo-Ora indicated the existence of the gene in the savanna woodland populations; earlier records were from the rain forest and Guinea savanna. The implications of these results, within the context of incipient speciation in Anopheles gambiae s.s. are discussed.